Politične ideje in družbeni koncepti slovenskega političnega katolicizma pred drugo svetovno vojno - Pelikan, Egon (Javnost (Ljubljana), 2010)
The article discusses attempts of Slovene political Catholicism in the1930s to restore Ancien Regime by establishing a model of estate corporatism which would negate parliamentarism, democracy, liberalism, socialism, and communism.Author identifies the origins of estate corporatism in three political and ideational sets: papal encyclicals, political ideas and patterns of other European authoritarian estate-corporatist dictatorships, and ideational imaginary of corporatism in the ideology of Italian Fascism. The structure of Slovene political Catholicism almost perfectly coincides with thestrategy which is used by the Catholic Church in Europe to cope with modernisation and secularisation; on the other hand, this structure lacks a solid ideological basis which causes fi rst discords in Slovene political Catholicism.
Keywords: Slovenia; Slovenija; politična zgodovina; politične stranke; political party; katolicizem; katolištvo; Catholicism